Left Atrial Transverse Diameter on Computed Tomography Angiography Can Accurately Diagnose Left Atrial Enlargement in Patients With Atrial Fibrillation. Issue 3 (May 2015) - Sohrabi, Sahand; Hope, Michael; Saloner, David; Keedy, Alexander; Naeger, David; Lorca, Maria Clara N.; Ordovas, Karen G.
<x xml:space="preserve">Abstract</x> Purpose: Left atrial (LA) enlargement is associated with increased risk for adverse cardiovascular events. We assessed the accuracy of LA transverse and antero-posterior (AP) diameters obtained from chest computed tomography (CT) angiography in patients with atrial fibrillation. Materials and Methods: Nongated contrast-enhanced 64-slice multidetector CT angiography (slice thickness of 0.625 to 1.25 mm) was used to measure the volume and transverse and AP diameters of the LA in 222 subjects. The internal contours of the LA and LA appendage were outlined in 1 of every 5 axial images, and the LA area was multiplied by 5 times the slice thickness. Maximum transverse and AP diameters of the LA were measured, excluding the appendage. Receiver operating characteristic curves were fitted to assess the accuracy of the diameters. A Wald test was used to compare the area under the curves. Results: The mean age of patients was 60.0±10.6 years, and 71% were male. Median LA volume was 55.9± 24.4 mL/m2. LA enlargement was present in 83% of the patients. Transverse and AP LA diameters were accurate estimators of the LA enlargement. The transverse diameter demonstrated higher accuracy than the AP diameter, with area under the curves of 0.89 (0.84 to 0.94) and 0.81 (0.73 to 0.89), respectively (P<0.05). A transverse LA diameter of 7.3 cm had a sensitivity and specificity of 85% for detection of LA enlargement. At the same sensitivity level, an AP diameter of 4.3 cm had a specificity of 60.5%. Conclusions: Transverse LA diameter can accurately detect LA enlargement in patients with atrial fibrillation. This parameter can be used for detection of patients with possible LA enlargement on chest CT angiography.